Control Of Shunt Converter For DPFC Distributed Power Transmission System - شعبان, فيصل; أبو طبق, نسمت; علي, احمد (Latakia University Journal -Engineering Sciences Series, 2022)
Flexible AC Transmission Systems (FACTS) are the best systems for controlling the power flow in electrical grids, but the difficulty of installing, designing and high their high price has significantly reduced their use. The recent emergence of the Distributed Static Series Compensator (DSSC) as a basic development of Static Synchronous Compensator (SSSC) has contributed to a significant development in the reduction of the design costs of this equipment, especially if the costs of manufacturing the Unified Power Flow Controller (UPFC), And Distributed Power Flow Controller (DPFC). In this research, we provided a control method in the Shunt Converter of the DPFC system based on finding the mathematical model represented to make this template, adjusting the PID controller parameters, and controlling the DC-Link continuous current effort on both ends of the capacitor effort used in the branching block, using radiological control, Pulse Width Modulation (PWM), and optimal lengthening method. Our results showed the ability of this method to accurately and effectively control the amount of reactive capacity provided by the branching mold of the network, and to automate the values required of it, as we were able through the method provided by DC-Link voltage control on the condenser of the branch template at fixed values, and adjust the efforts of the electrical transport network bars. The recent emergence of the DSSC as a basic development of SSSC has contributed to a significant development in the reduction of the design costs of this equipment, especially if the costs of manufacturing the UPFC unified regulator are considered as the best FACTS devices, especially the recent development that led to the emergence of the DPFC distributed regulator.